A CONDIÇÃO (PRÓPRIA): CONCEITO, MODALIDADES, PENDÊNCIA, VERIFICAÇÃO E EFICÁCIA — um estudo jurídico-comparativo do regime jurídico português e inglês: Miguel de Azevedo Moura (De Legibus - Law Journal, 2021)
The purpose of the present study is to provide a legal comparative analysis of the contingent condition regimen — contractual term on which certain effects of the contract are subject to a future and uncertain event — of both Portuguese and English legal system. The five elements subject to analysis and included within the syntagmatic axle are the following: concept, classes, pendency, occurrence and non-occurrence of the event and effects. Quantitatively, it was found more similitudes than differences. Notwithstanding, differences noted are relevant regarding the dogmatical framework of the object.
Keywords: Private Comparative Law; Contingent Condition; Contract Law; Private Law; Portuguese Law; English Law